Distinguished leadership behaviours and styles of basketball coaches in UAE universities - El-Saleh, M. S.; Althawabeyeh, M. M. (Journal of Human Sport & Exercise, 2020)
This study aims to identify the distinguished leadership behaviours and styles of basketball teams` coaches in UAE universities. The researchers have adopted a descriptive method through using surveying methodology, which suites the nature of the study. The sample of the study consists of 60 male and female players of the university teams participating in the Abu Dhabi Inter-University Sports League (ADISL) for the 2018/2019 sports season, who have been randomly selected. They all responded to the modified Scale Assessing Leadership Behaviour of Coaches, used by Mustafa Abu Zeid (1999), which consists of 55 paragraphs. After collecting the data and conducting the necessary statistical processes, the researchers have concluded that the leadership behaviour of basketball coaches in UAE universities changes in training and matches in contrast with the Scale dimensions. They have also concluded that attention to health aspects, athletic performance, and social as well as democratic recognition are the most common and most common methods used by the coaches. In light of the findings, the researchers have recommended that coaches should use the democratic style of leadership due to its appropriateness for the nature of players` way of thinking in universities, avoid the dictatorial leadership style and pay heed to motivation and equity among players. The researchers also recommend that the study findings should be generalized to the Higher Education Sports Federation (HESF) and the UAE Basketball Association, conduct similar studies for coaches of other games and organize training courses for university coaches on the most important and new methods of sports training and leadership.